Treating Adolescent Depression: Exploring Neurofeedback Training, Dhikr, and Community Stigma in Complementary Therapies (A Case Study) - Oktaviyantini, Tri (Preventia: The Indonesian Journal of Public Health, 2024)
Adolescent depression, particularly when complicated by psychotic features, presents significant challenges in treatment due to its complex and multifaceted nature. This case study explores the integration of neurofeedback training and Dhikr, an Islamic meditative practice, as complementary therapies alongside traditional pharmacotherapy in treating a 15 years old male diagnosed with severe recurrent depression. Despite initial reluctance and skepticism influenced by community stigma surrounding mental health and spiritual practices, both therapies contributed to noticeable improvements in the patient's symptoms and overall well-being. Neurofeedback was utilized to regulate brainwave activity, while Dhikr provided a meditative and spiritual component that promoted mindfulness and inner peace. The case highlights the importance of addressing community stigma, personalized treatment plans, and holistic approaches in managing adolescent depression, ultimately leading to better engagement and therapeutic outcomes.